RISK FACTORS AND OUTCOMES OF NEW ONSET ARRHYTHMIA IN SURGICAL INTENSIVE CARE UNIT: A RETROSPECTIVE STUDY: New Onset Arrhythmia - Hanif, Sadaf; Shamim, Faisal; Sohaib, Muhammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the frequency of new-onset cardiac arrhythmias among patients admitted in surgical intensive care unit as well as associated risk factors. Study Design: Retrospective observational study. Place and Duration of Study: Surgical Intensive Care Unit, Aga Khan University Hospital, Karachi, from Jan 2018 to Dec 2019. Methodology: The medical record numbers of all patients admitted in surgical intensive care unit were obtained from Surgical intensive care unit case log entries and reviewed. Patients` and healthcare providers` identification were kept confidential. Data was analyzed using SPSS version 19. Results: Only 13/1076 patients included in the study had cardiac arrhythmias during their stay in Surgical intensive care unit. Among all patients with arrhythmias (n=13), atrial fibrillation was the most common type of arrhythmia 7 (53.8%). The study found higher occurrence of arrhythmias among the patients in the age category of 66 years or above 8 (4.6%) and when compared to younger patients with age categories 18-40 years 2 (0.3%) and 41-65 years 3 (0.3%) respectively (p-value<0.05). Similarly, arrhythmias were higher among patients who had relatively prolong intensive care unit stay and post-operative status as the primary cause of intensive care unit admission. Conclusion: Occurrence of cardiac arrhythmias is relatively low among patients admitted to surgical intensive care patient population. Patients age (>65 years), prolong intensive care unit stay, post-operative status are positively associated with development of cardiac arrhythmias among critically ill patients admitted in surgical intensive care unit.